THE IMPACT OF REVISION STRATEGIES ON UNIVERSITY STUDENTS’ WRITING - Anselmus Sudirman; Luky Tiasari (LP2M Universitas Sarjanawiyata Tamansiswa, 2016)
The objectives of this study are (1) to describe the most frequently employed revision strategies used by university students in their research proposals, and (2) to describe the problems they face in revising their research proposals. This considers the revision strategies as part of the research proposals writing by examining how a focus on deletion, substitution, addition and reordering affects the revising processes ofwritten products. The method used in this study was a qualitative research fundamentally involved an in-depth interpretation of data. Four university students at PBI UST academic year of 2015/2016 involved in this study used different revision strategies: (a) revising by deletion, (b) revising by substitution, (c) revising by addition and (d) revising by reordering. An open ended interview technique was used to get information on problems the participants faced during writing and revising their research proposals. The processes of data analysis technique were (1) establish units of analysis of revision strategies, indicating how these units are similar to and different from each other, (2) match the responses given in interviews to written documents, (3) create a domain analysis, and (4) establish relationships and linkages between the domains (Manion & Morrison, 2000). The findings show that participants revised their research proposals by using a deletion strategy through which they focus on removing certain parts of the proposals being produced. Another revision strategy is substitution in which participants organize replacements of inappropriate parts of the proposals. The revision strategy called addition is used to refer to certain missing parts of proposals. The simultaneous use of reordering is also of paramount importance to mark the revised source materials in the writing activities. Emergent revision strategies were coined byparticipants namely revision by consultation, revision by rereading and reanalyzing, and revision by reviewing. Participants faced grammatical errors (grammatical difficulties), lack of vocabulary, incorrect use of dictions and sentences (a word-level and a sentence-level of difficulties) in the process of writing their research proposals.Keywords: revision strategies, deletion, substitution, addition, reordering